2020
DOI: 10.1097/ncq.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge of Opioids

Abstract: Background: The opioid crisis has influenced practice changes to mitigate risks to patients receiving opioids. It is essential that nurses understand contemporary guidelines to provide safe patient care for patients receiving opioids. Purpose: This study was designed to assess general knowledge of opioids among nurses in nonprescribing patient care roles. Methods: A survey was developed, validated, and deplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Similar knowledge gaps exist in nursing education (Kaiser, 2020). The literature supported negative attitudes of nurses towards individuals with OUD led to feelings of marginalization and contributed to decisions to delay healthcare and specifically, treatment for OUD (Dion, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Similar knowledge gaps exist in nursing education (Kaiser, 2020). The literature supported negative attitudes of nurses towards individuals with OUD led to feelings of marginalization and contributed to decisions to delay healthcare and specifically, treatment for OUD (Dion, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…Hemşirelerin tamamı multimodal analjezi ile ilgili bir eğitime katılmamış olup, bu konu ile ilgili eğitim almak istediklerini bildirmiştir. Ameliyat sonrası ağrı ile ilgili yapılan çalışmalarda 12,19 hemşirelerin çoğunluğunun ağrı kontrolü ile ilgili bir eğitim almadığı belirlenmiş, diğer yandan Kaiser 23 hemşirelerin yarısının son 6 ayda multimodal analjezi eğitimi aldıklarını raporlamıştır. Yin ve Wong'un 27 18 çalışmayı değerlendirdiği sistematik derlemede hemşirelerin ağrıya yönelik eğitim almalarının ağrı yönetimi için önemli olduğu vurgulanmıştır.…”
Section: Tartişma Ve Sonuçunclassified
“…[14][15][16] Buna karşın sınırlı sayıda yapılan çalışmalar hemşirelerin postoperatif ağrı, analjezik ajan ile nonfarmakolojik yöntemlere yönelik bilgilerinin yetersiz olduğunu raporlamıştır. [17][18][19][20][21] Türkiye'de 22 ve Ethopya'da 20 yapılan iki çalışmada hemşirelerin multimodal analjeziye yönelik bilgisinin olmadığı, Avrupa'da 23 Evren ve Örneklem: Çalışmanın evrenini tüm cerrahi klinikler ile cerrahi yoğun bakım ünitelerinde en az 6 ay çalışan toplam 150 hemşire oluşturdu (N=150). Evrenin tamamına ulaşılması hedeflenmesine karşın, COVID pandemisi nedeniyle çalışmanın yapılacağı tarih aralığında izinli veya raporlu olmayan, çalışmaya katılmaya istekli ve onam veren 140 cerrahi hemşiresi çalışma kapsamına alındı.…”
Section: Introductionunclassified
“…2 Studies show an association between patients who underwent a surgical procedure and a higher risk for ORADEs. [2][3][4][5][6][7] Kessler et al reported that 13.6% of postoperative inpatients experienced a documented ORADE. 3 The Institute for Healthcare Improvement {IHI} suggests ORADEs may imply opioid-related adverse drug events since naloxone…”
Section: Introductionmentioning
confidence: 99%
“…Studies show an association between patients who underwent a surgical procedure and a higher risk for ORADEs 2-7. Kessler et al reported that 13.6% of postoperative inpatients experienced a documented ORADE 3…”
Section: Introductionmentioning
confidence: 99%